2020
DOI: 10.1186/s13011-020-00269-3
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol consumption and its associated factors among pregnant women in Sub-Saharan Africa: a systematic review and meta-analysis' as given in the submission system

Abstract: Background: Alcohol consumption during pregnancy represents a significant public health concern. It has several adverse health effects for both the mother and the developing fetus. This study aimed to estimate the pooled prevalence and the effect size of associated factors of alcohol consumption during pregnancy in Sub-Saharan Africa countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 65 publications
6
41
2
Order By: Relevance
“…In previous local studies, the prevalence of alcohol use during pregnancy varied from 4.3-45% [10,18], which is consistent with the national survey. However, the prevalence is higher compared to a recent meta-analysis in sub-Saharan Africa [20.8% (95% CI: 18.2, 23.5)] [22], the World Health Organization Africa region (18.5%) [23], Korea (16.4%) [24], the United States (11.5%) [25], and global estimated prevalence (9.8%) [26]. On the other hand, this nding is lower than studies done in Australia (64%) [27] and Russia (60%) [28].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In previous local studies, the prevalence of alcohol use during pregnancy varied from 4.3-45% [10,18], which is consistent with the national survey. However, the prevalence is higher compared to a recent meta-analysis in sub-Saharan Africa [20.8% (95% CI: 18.2, 23.5)] [22], the World Health Organization Africa region (18.5%) [23], Korea (16.4%) [24], the United States (11.5%) [25], and global estimated prevalence (9.8%) [26]. On the other hand, this nding is lower than studies done in Australia (64%) [27] and Russia (60%) [28].…”
Section: Discussioncontrasting
confidence: 64%
“…Findings of a systematic review showed that alcohol consumption during pregnancy was associated with socioeconomic factors, like source of income, employment status, and knowledge of harmful effects of alcohol; and behavioral factors, like prior alcohol consumption, partner's alcohol use, peer pressure to use alcohol, and smoking [22]. Other studies show that women's alcohol drinking has been increasing due to having their own income, socialization with friends, peer pressure, and lack of adequate information about the adverse health effect of alcohol [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It is disturbing that most of the pregnancies are not planned and that could predispose the embryo to alcohol during early pregnancy [74,75]. Unplanned pregnancies constituted over a half of the total among women in this study, and the necessity to reduce unplanned pregnancies has been suggested by other researchers [5]. Lack of proper information on the possible health outcomes of alcohol use by potential mothers, and related fatal consequences, exacerbates drinking among women of reproductive age, leading to growth problems and morbidity and mortality among infants [14,41].…”
Section: Discussionmentioning
confidence: 70%
“…Tobacco and alcohol are the psychosocial factors contributing to public health issues in low and middle-income countries (LMICs) [ 1 , 2 , 3 , 4 ]. In Africa, the prevalence of alcohol use during pregnancy ranges from 4.30% to 59.28%, and varies within and across countries, while in Sub-Saharan Africa (SSA), the prevalence has been estimated between 4.30% and 59.28% [ 5 ]. These variations have been reported to originate from factors, such as maternal drinking behaviors, environmental, policy, and cultural differences [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], we have been notified that there is a mistake in the title of the article.…”
mentioning
confidence: 99%